POWER, TRADITION, AND IDENTITY IN CLASSICAL QUR’ANIC EXEGESIS: THE LOCALITY OF IBN KATHĪR’S INTERPRETATION AND ITS RELEVANCE TO QIRĀ’AH SAB’AH - Mabrur, Mohammad Safwan (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2024)
This article explores how the socio-intellectual environment of 14th-century Damascus shaped Ibn Kathīr’s preference for certain Qur’anic readings (qirā’ah sab’ah) and his rejection of others. While existing studies often examine qirā’ah through philological or theological lenses, few have contextualized them sociologically in relation to local power dynamics. This research addresses that gap by analyzing the interplay between Ibn Kathīr’s locality, interpretive methodology, and authority structures using Pierre Bourdieu’s habitus theory and Max Weber’s conflict of authority. Employing a qualitative approach that integrates textual analysis, historical study, and sociological theory, this study finds: (1) The Damascene scholarly habitus—marked by the dominance of the Ahl al-Hadith tradition and Shafi’ī jurisprudence—formed Ibn Kathīr’s preference for mutawātir qirā’ah like Hafs’s narration from ‘Āsim; (2) Conflicts of religious authority, including tensions with minority sects and Mamluk political structures, catalyzed the exclusion of qirā’ah shādzah such as arjulakum in QS. Al-Mā’idah (5): 6; and (3) Qirā’ah sab’ah functioned as an arena for the negotiation of Sunnī identity, balancing hermeneutic flexibility and theological orthodoxy. This study contributes a novel sociological perspective to tafsir studies, demonstrating that Qur’anic interpretation is not a neutral act, but a socially embedded practice shaped by context, power, and identity.